SELF-HARM BEHAVIOR AMONG TEENAGER AND FATHER’S INVOLVEMENT IN PARENTING: A CROSS-SECTIONAL STUDY - Ismah, Zata; Sinaga, Haryanti; Despiana, Dwi (Journal of Community Mental Health and Public Policy, 2025)
Background: A meta-analysis conducted in 2019 reported that 22.1% of individuals engaged in self-harming behaviors, with 17% of these cases occurring among adolescents. However, empirical research examining the association between paternal involvement and adolescent self-harm remains limited, warranting further investigation. Purpose: This study aims to assess paternal role in relation to self harm. Methods: A cross-sectional study was conducted in Medan, Indonesia, involving a sample of 1,221 high school students. Data collection utilized the Self-Harm Inventory (SHI). Statistical analyses included proportion and central distribution tests, one-way ANOVA, and Pearson correlation. Results: The findings reveal a statistically significant association between paternal involvement and self-harm behavior. Adolescents experiencing fatherlessness were found to be 15.42 times more likely to engage in self-harming behavior compared to those with positively involved fathers. Furthermore, a negative correlation was observed between paternal involvement and self-harm scores, indicating that reduced paternal engagement is associated with higher levels of self-harming behavior among adolescents. Conclusion: The absence of a father figure or inadequate paternal involvement is significantly associated with increased self-harm behavior in adolescents. These findings underscore the need for targeted interventions, including psychotherapeutic support and active involvement of close family members, to mitigate self-harm among this vulnerable population. Abstrak Latar belakang: Dalam meta-analisis tahun 2019 melaporkan terdapat 22,1% orang melukai diri sendiri (Self-harm) dan 17% diantaranya dilakukan oleh remaja. Minimnya penelitian keterlibatan ayah dengan terjadinya Self-harm pada remaja, sehingga penelitian ini perlu dilakukan. Tujuan: penelitian ini bertujuan menganalisis bagaimana peran ayah dalam hubungannya dengan Self-harm. Metode: desain cross sectional digunakan dalam penelitian ini yang dilakukan di Kota Medan. dengan sampel yang ditentukan sebanyak 1,221 siswa menengah atas. Instrumen yang digunakan Self-harm Inventory (SHI). Analisis yang digunakan yaitu uji proporsi dan distribusi central, one-way ANOVA dan Pearson Correlation. Hasil: Terdapat hubungan yang signifikan antara fathering dengan Self-harm. Remaja yang mengalami fatherless akan berisiko 15,42 kali melakukan Self-harm pada dirinya dibandingkan ayah yang berperan positif. Juga ditemukan hasil korelasi negatif antara fathering dengan Self-harm, dimana semakin kurang peran ayah maka semakin tinggi skor perilaku self-harm remaja. Kesimpulan: Ketidakhadiran ayah berhubungan dengan terjadinya Self-harm pada remaja. Temuan ini menggarisbawahi perlunya dirumuskan intervensi, seperti dukungan psikoterapi dan keterlibatan aktif anggota keluarga terdekat, untuk mengurangi tindakan menyakiti diri sendiri didalam populasi rentan tersebut.